Strategic Management at the Zainuddin Abdul Madjid International Airport during the COVID-19 Pandemic - Supardi, Rai Edy; Utami, Vidya Yanti; Dewi, Dhea Candra (Jurnal Studi Ilmu Pemerintahan, 2023)
This research aims to analyze the strategic management at the Zainuddin Abdul Madjid International Airport Branch Office in Lombok Praya during the newly emerged pandemic era. The data analysis method used is a descriptive method with a qualitative approach. Observations, interviews, and documentation were carried out in order to collect data and then analyzed with an interactive data collection model, data conversion, data presentation, and data verification. The results of the research indicate that the implementation of strategic management is carried out by PT. Angkasa Pura I, specifically the Zainuddin Abdul Madjid International Airport Branch Office, was carried out well according to the strategic management theory, which is formulation, implementation, and evaluation. The management strategy is carried out through efforts to prevent and control the outbreak, in addition, a cost leadership and revenue enhancement program is also carried out as a step to achieve efficiency and increase revenue by looking at available opportunities through the formation of teams according to their respective tasks and functions, so as to speed up the handling of the impact of the COVID-19 pandemic on the company's performance.